Escape from the carnival of horrors - Stine, R. L. (New York : Scholastic, 1995)
Following the instructions, readers choose from over 20 adventures in the annual carnival. Each has a different scary ending.
RL4.
008-012.
490
Keywords: Carnivals -- Juvenile fiction; Horror fiction